Mf Delicious Ice Cream Café / Nur Zafirah Auni Mohd Zamri - Mohd Zamri, Nur Zafirah Auni (2020)
This case study report is for the Fundamentals of Entrepreneurship (ENT300), consists of the information and the analysis of one business that has been chosen. During this pandemic season, I use several platforms in internet such as Facebook, Google and also Instagram for collecting the information that required to be added in this case study. Based on those platforms and social medias that I use followed by my observation, I have received some information about the business’s background, organizational structure, the profile of the entrepreneur or the owner of the business and also the products of the business followed by the services served by the business. I also managed to get the photos of the premise, the owner and also the products of the business. Besides, based on my research on this business, I managed to investigate several entrepreneurial characteristics or PEC (Personal Entrepreneurial Competencies) of this business that I have choose.